Pengaruh Harga, Kualitas Barang Terhadap Keputusan Pembelian Air Mineral AQNU (Studi Kasus Pada Mahasiswa Universitas Islam Malang - Muhammad Habibullah Nur Ihsan; Khalikussabir Khalikussabir; Ratna Tri Hardaningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract This study  to examine the influence of price and product quality on purchasing decisions of AQNU bottled water (A case study on students of Universitas Islam Malang). The population in this study consists of students from Universitas Islam Malang. The sampling technique used is non-probability sampling with a purposive sampling approach. Data collection was conducted using a questionnaire method. The sample size was determined using the Slovin formula, resulting in 100 respondents. The sample characteristics include students who have purchased AQNU bottled water products at least twice. Keywords: Behavior Finance, Knowledge Investment, Tolerance Risk, Investment Decisions, Theory Of Panned Behavior